The Value and Significance of New Quality Productivity in Empowering High-Quality Development of Youth Sports Training - Yang, Yi; Liu, Congbing (Pedagogy and Psychology of Sport, 2026)
Extracurricular sports training serves as a vital pathway for the positive development of youth. This paper employs literature review and logical analysis to explore how new-quality productive forces empower the high-quality development of the youth sports training industry. The research concludes that new-type productive forces play a significant role in empowering the high-quality development of youth sports training. Its specific value and significance are manifested in: enhancing teaching quality, optimizing resource allocation, and promoting industrial innovation, thereby advancing the upgrading of youth sports training; simultaneously, it meets the diverse sports needs of young people, elevates their sports literacy, and lays a foundation for the long-term development of the sports sector; the integration of new-type productive forces is a crucial pathway for building a sports powerhouse and fulfilling the sports demands of the populace.